Phytochemicals based chemopreventive and chemotherapeutic strategies and modern technologies to overcome limitations for better clinical applications. (12th September 2019) - Singh, Vipendra Kumar; Arora, Deepika; Ansari, Mohammad Imran; Sharma, Pradeep Kumar
Abstract : Naturally occurring phytochemicals or plant derivatives are now being explored extensively for their health's benefits and medicinal uses. The therapeutic effect of phytochemicals has been reported in several pathophysiological settings such as inflammatory disorders, metabolic disorders, liver dysfunction, neurodegenerative disorders, and nephropathies. However, the most warranted therapeutic effects of phytochemicals were mapped to their anticancerous and chemopreventive action. Moreover, combining phytochemicals with standard chemotherapy has shown promising results in cancer therapy with minimal side effects and better efficacy. Many phytochemicals, like curcumin, resveratrol, and epigallocatechin‐3‐gallate, have been extensively investigated for their chemopreventive as well as chemotherapeutic effects. However, poor bioavailability, low solubility, hydrophobicity, and obscure target specificity restrict their therapeutic applications in the clinic. There has been a continually increasing interest to formulate nanoformulations of phytochemicals by using various nanocarriers, such as liposomes, micelles, nanoemulsions, and nanoparticles, to improve their bioavailability and target specificity, thereby maximizing the therapeutic potential. In the present review, we have summarized chemopreventive as well as chemotherapeutic action of some common phytochemicals and their major limitations in clinical application. Also, we have given an overview of strategies that can improve the efficacy of phytochemicals for their chemotherapeutic value in clinical settings.